2019
DOI: 10.1029/2019gl082687
|View full text |Cite
|
Sign up to set email alerts
|

Steve: The Optical Signature of Intense Subauroral Ion Drifts

Abstract: Little is currently known about the optical phenomenon known as Steve. The first scientific publication on the subject suggests that Steve is associated with an intense subauroral ion drift (SAID). However, additional inquiry is warranted as this suggested relationship as it is based on a single case study. Here we present eight occurrences of Steve with coincident or near‐coincident measurements from the European Space Agency's Swarm satellites and show that Steve is consistently associated with SAID. When sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
106
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 42 publications
16
106
0
Order By: Relevance
“…Gallardo‐Lacourt et al () related various properties of the observed STEVEs to the general state of the Earth's geomagnetic environment and reinforced the relationship of STEVE occurrence in conditions favorable for SAIDs. A recent study by Archer et al () confirmed this association by examining 122 SAID occurrences, finding that STEVE occurred only for the most intense SAIDs, namely, those with large plasma velocities, high electron temperatures, and low electron densities.…”
Section: Introductionmentioning
confidence: 85%
“…Gallardo‐Lacourt et al () related various properties of the observed STEVEs to the general state of the Earth's geomagnetic environment and reinforced the relationship of STEVE occurrence in conditions favorable for SAIDs. A recent study by Archer et al () confirmed this association by examining 122 SAID occurrences, finding that STEVE occurred only for the most intense SAIDs, namely, those with large plasma velocities, high electron temperatures, and low electron densities.…”
Section: Introductionmentioning
confidence: 85%
“…SAR arcs are found inside plasma density troughs of ne3×104 cm 3 and Tefalse(3÷5false)×103 K related to subauroral polarization streams (SAPS) with flow speeds vd0.5–1 km/s (e.g., Foster et al, ; Förster et al, ; Baumgardner et al, ). The STEVE‐related SAID channels (MacDonald et al, ; Nishimura et al, ; Archer et al, ) have higher Te up to 104 K, larger speeds, vd4–6 km/s, and deeper troughs, ne<104 cm 3.…”
Section: On the Steve Spectrummentioning
confidence: 99%
“…Skyglow in the form of a narrow in magnetic latitude, east‐west‐aligned mauve “ribbon” and occasionally green rayed “Picket Fence” equatorward of the auroral zone was often reported by amateur photographers. MacDonald et al () have named the mauve arcs as Strong Thermal Emission Velocity Enhancement (STEVE) because of the relation to strong plasma streams – subauroral ion drifts (SAID), with highly elevated electron temperature, Te5000 K. Their features have been detailed by Gallardo‐Lacourt, Liang, et al (), Gallardo‐Lacourt, Nishimura, et al (), Nishimura et al (), and Archer, Gallardo‐Lacourt, et al (). In particular, Gallardo‐Lacourt, Nishimura, et al () statistical study shows that STEVE occurred during the recovery phase of substorms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the strong thermal emission velocity enhancement (STEVE) has been found to be a subauroral optical feature associated with SAID with larger magnitudes than average SAID (Archer et al, 2019; MacDonald et al, 2018). Since plasma flow measurements are often limited in space and time, the optical signature can be useful for finding when and where intense SAID exist.…”
Section: Introductionmentioning
confidence: 99%